Reality about pain control: The knowledge and beliefs of nurses on the nature, assessment and management of pain [Aǧri kontrol gerçeǧi: Hemşirelerin aǧrinin doǧasi, deǧerlendirilmesi ve geçirilmesine ilişkin bilgi ve inançlari] - (:unkn) unknown (My University, 2005)
The present research was conducted descriptively to define the approaches of nurses to the nature of pain, its assessment, and management. The research was carried out in October 2001 in Antalya with a scope of 227 nurses attending to the Second National Clinician Nurses' Congress. Initial aim was to include all 286 nurses attending the congress, however, because 59 nurses refused to participate, the number of the participants finalized as 227. A data gathering form of 20 questions was used. Results were presented in percentages. At the end of the research, though the knowledge the nurses had on the nature of pain was satisfactory, their attitudes related with pain assessment and management were noted to be below expectations. These results point out a void in the nurses' knowledge pertaining to pain management. As a result, we consider imperative that the nurses should acknowledge the significance of pain and should improve their professional attitudes and knowledge in order to gain control over pain through a multidisciplinary approach and to prove the caicial and inevitable role of nurses in such a team.
Keywords: Nursing; Pain; Pain assessment; Pain management